Antifungal Activity of Endophytic Bacteria Isolated from Dayak Onion (Eleutherine bulbosa) Against Candida albicans - Krestina, Widya; Mutiasari, Dian; Panjaitan, Desimaria; Wardhana, Vinsen Willi; Zulviana; Rahmawati, Maynissa; Naibaho, Frans Grovy (Departemen Biologi, Institut Pertanian Bogor, 2024)
Candidiasis is a fungal infection due to a decrease in the immune system caused by Candida spp. In general, candidiasis is treated with antifungal drugs, but uncontrolled use can result in the emergence of drug resistance and toxicity. Endophytic bacteria have the potential to be biological control agents against various fungal infections including candidiasis. This study aims to determine the antagonistic activity of endophytic bacteria isolated from Dayak onions and the antifungal activity of its cell-free supernatant (CFS) against Candida albicans. Thirteen isolate strains of endophytic bacteria were used in this study. Antagonistic activity was tested using the agar plug diffusion method. Endophytic bacteria that showed antagonistic activity against C. albicans were cultivated in Nutrient Broth media to produce CFS. The antifungal activity of CFS was tested using the Kirby–Bauer disk diffusion method. The results indicated that six isolates of endophytic bacteria from dayak onions have antagonistic activity against C. albicans. CFS from strain CED4 has a strong antifungal activity against C. albicans with a clear zone diameter of 18.5 mm. Further studies are needed to determine the antifungal compounds produced by CED4 isolates for the development of anticandidal.